Visual and refractive outcome, higher order aberrations and complications following intraocular lens exchange in eyes without comorbidities - Henningsen, Nikola; Khoramnia, Ramin; Auffarth, Gerd U.; Köppe, Maximilian; Łabuz, Grzegorz; Yildirim, Timur Mert (Scientific reports, 2025)
Intraocular lens (IOL) exchange is performed to treat severe IOL-related complications. There is little published data on the impact of this procedure on the refractive outcomes and intra- and postoperative complications, especially in otherwise healthy eyes. We investigated the refractive outcome of IOL exchange surgery, including corneal aberrations; additionally, we assessed the influence of different IOL characteristics on intraoperative and postoperative complications. This prospective clinical study included 35 eyes with homogenous IOL calcification without other ocular pathologies. Using Pentacam AXL Wave (Oculus Optikgeräte GmbH, Wetzlar, Germany), corrected distance visual acuity (CDVA), target refraction compared to the postoperative spherical equivalent, corneal topography and lower and higher-order aberrations were assessed preoperatively and from 3 months after surgery. Intraoperative and postoperative complications were recorded and compared between different IOL characteristics. The secondary IOL in 53% of cases, was a retropupillary iris-fixated Artisan Aphakia (Ophtec BV, Groningen, Netherlands), 37% had a sulcus-fixated AR40e (Johnson & Johnson Vision, Irvine, USA), and 10% had a capsular bag IOL. The CDVA improved from 0.16 ± 0.14 to 0.07 ± 0.14 logMAR (p = 0.04). In most cases, the target refraction was within ± 1.0 D (Artisan: 71%, AR40e: 90%, Capsular: 100%). IOL exchange did not induce relevant change in corneal aberrations. Anterior (81%) and posterior (78%) vitrectomy were performed in most cases. The haptic design of the primary IOL did not impact intra- or postoperative complications. Although exchanging an IOL involves greater surgery compared to the initial IOL implantation, visual and refractive outcomes are good, and the exchange does not cause relevant change in aberrations. Intra- and postoperative complications are mostly mild and resolve without sequelae.